Producer-led scaling with pioneer positive deviance in animal health, feed and forage, and social norms for increased climate resilience. - Worku, Tigist; Habermann, Birgit; Getahun, Elizabeth; Lemma, Mamusha; Adie, Aberra; Alemu, Biruk G.; Berhanu, Dagim; Derseh, Melkamu; Jemberu, Wudu T.; Knight-Jones, Theodore J.D.; Achandi, Esther (International Livestock Research Institute, 2025)
The Sustainable Animal and Aquatic Foods (SAAF) and Climate Action Science Program, in collaboration with the RESTORE Project, is implementing the component “Pastoral System – Producer-led Scaling of Climate-Resilient Practices” in Ethiopia to strengthen resilience and productivity in livestock-dependent pastoral communities. To support this effort, a National Stakeholder Engagement Workshop was held on 27 November 2025 at the ILRI Campus in Addis Ababa to present and discuss the Pioneer Positive Deviance (P-PD) approach, share findings from ongoing implementation in pastoral systems, and gather feedback for improving and institutionalizing the approach within Ethiopia’s pastoral extension system. The workshop brought together 23 participants from government institutions, research organizations, NGOs, development partners, and civil society. Key sessions included presentations of the P-PD guideline for practitioners, feedback through a Troika-format discussion, presentation of Phase 1 findings from South Omo and Afar, World Café group discussions, exploration of synergies with the Farmers’ Field School approach, and structured feedback on a forthcoming Training of Trainers (ToT) guideline. Discussions highlighted both the feasibility of applying P-PD in pastoral contexts and the need for careful adaptation to communal governance structures, mobility, customary institutions, gender norms, and indigenous communication systems such as “Dagu”. Participants emphasized the importance of contextualization, co-design with pastoral communities, experiential and practice-oriented training, and alignment with national and pluralistic extension systems. Strong demand was expressed for capacity building and ToT programs adapted to pastoral systems. The workshop concluded with clear recommendations for refining the P-PD and ToT guidelines, strengthening partnerships, expanding evidence generation, and supporting coordinated implementation to enhance producer-led scaling, social learning, and locally led adaptation in Ethiopia’s pastoral systems.